Architecture and Green Building Practices: A Perspective of Sustainable Development - Bhandari, Diksha (Journal of UTEC Engineering Management, 2025)
Green architecture, also known as "sustainable architecture" or "green building," is a multi-aspect method of approaching the idea generation, scientific analysis, and design of the built environment where environmental sensitivity, resource conservation, and energy efficiency are indivisibly woven together.This review discusses the evolution, principles, and benefits of sustainable architecture, enumerating its use in solving environmental, social, and economic challenges of contemporary construction practices. The evolution from conventional energy utilization to the environmentalist movement of the twentieth century is discussed, along with it marking a transition towards green building technology, particularly post-1970s energy crisis. The key characteristics of green architecture, water conservation, energy efficiency, sustainable materials, indoor environmental quality, and waste management are covered together with their application through technologies like renewable energy systems, rainwater harvesting, and recycled materials. The research also identifies the visual value of green designs, reconciling Biophilic principles and indigenous materials to bring buildings into harmony with their environments (Tabb & Deviren, 2017). Green buildings are examined for social, economic, and environmental advantages, with findings indicating high energy and water conservation, healthier occupants, and more ecological balance. This research reiterates the role of sustainable architecture in playing a part in achieving the Sustainable Development Goals, pushing for ongoing innovation and cooperation.